Effect of water deprivation for three consecutive days on the proportions of androgen receptor-immunolabeled supraoptic nucleus magnoneurons in Wistar rats - Chetoui, Samir; Touati, Hanane; Remana, Soumia; Benhaferi, Nadir; Hanniche, Nadia; Talmatamar, Amina; Benarab, Souhila; Bougrid, Abdelkader (Acta Biologica Szegediensis, 2023)
The androgen receptor is an androgen-dependent transcription factor that belongs to the nuclear receptor superfamily. When the androgen receptor is not bound to its ligand, it is mainly localized in the cytoplasm, bound to chaperone proteins, which stabilizes its inactive conformation and confers a high affinity for the ligand. The conformational change of the androgen receptor begins when the androgen molecule binds to the receptor, which subsequently homodimerizes and it is actively translocated to the nucleus. In the nucleus, the receptor homodimers bind to androgen target genes, resulting in responses such as growth and survival. In this study, we used the immunohistochemistry technique to look for the proportions of androgen receptor-immunolabeled magnoneurons categories according to the sub-cellular localization of the receptor, in the supraoptic nucleus of control (tap water + ad-libitum food) and dehydrated male rats by tap water deprivation for three consecutive days. Our results show that the proportions of androgen receptor-immunolabeled magnoneurons would depend on the hydration status of the rats (Chi-square test of independence, P < 0.001), but this dependence relationship is weak (Cramer’s v value is equal to 0.30). Indeed, based on the results of our study, we hypothesized that dehydration by water deprivation for three consecutive days in adult male rats acts mainly on both of nuclear and cytoplasmic magnoneurons categories and has very little influence on the nucleocytoplasmic magnoneurons category. The effect could be due to activation of the entry of cytoplasmic non-androgen bound androgen receptors into the nucleus, activation of degradation of nuclear non-androgen bound androgen receptors, and inhibition of the binding of androgen molecules to androgen receptors.